2011
DOI: 10.1128/jvi.05312-11
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-Reactive HIV-1-Neutralizing Human Monoclonal Antibodies Identified from a Patient with 2F5-Like Antibodies

Abstract: The genes encoding broadly HIV-1-neutralizing human monoclonal antibodies (MAbs) are highly divergent from their germ line counterparts. We have hypothesized that such high levels of somatic hypermutation could pose a challenge for elicitation of the broadly neutralizing (bn) Abs and that identification of less somatically mutated bn Abs may help in the design of effective vaccine immunogens. In a quest for such bn Abs, phage-and yeast-displayed antibody libraries, constructed using peripheral blood mononuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 22 publications
(27 reference statements)
2
89
1
Order By: Relevance
“…Different studies have suggested that antibody polyreactivity contributes to neutralization of HIV-1 (24,27,31,(55)(56)(57)(58). Several mechanisms have been proposed to explain the role of antibody polyreactivity in HIV-1 neutralization.…”
Section: F425mentioning
confidence: 99%
“…Different studies have suggested that antibody polyreactivity contributes to neutralization of HIV-1 (24,27,31,(55)(56)(57)(58). Several mechanisms have been proposed to explain the role of antibody polyreactivity in HIV-1 neutralization.…”
Section: F425mentioning
confidence: 99%
“…1 A) overlaps that of 4E10 (39). While the epitope for m66.6 overlaps substantially with that of 2F5, this MAb is less potent and broad, neutralizing only a subset of the 2F5-sensitive viruses (64). The heavy-chain variable domains of all four Nt Abs are highly mutated and possess an unusually long third complementaritydetermining region of the antibody heavy chain (CDR-H3).…”
mentioning
confidence: 99%
“…Roughly half of the residues within this region are hydrophobic, and the MPER plays a crucial role in the fusion of the viral and cellular membranes (43). In addition, Nt epitopes within the MPER are targeted by two well-characterized broadly Nt (bNt) monoclonal Abs (MAbs) (4E10 and 2F5) (4,15,32,67) and two MAbs (Z13e1 and m66.6) that neutralize a range of viral isolates but are not bNt, making this region a promising target for vaccine efforts (39,64).…”
mentioning
confidence: 99%
“…The antigens specifically reacted with 2F5, 4E10 and a serum against the E1 domain and were immunogenic in rats generating antibodies targeting an epitope overlapping with the 2F5 epitope; however, they did not prevent HIV-1 infection in a TZM-bl based neutralisation assay. The antigens comprised the HIV-1 MPER-derived E2 domain because the corresponding bnAb antibodies are characterised by strong somatic mutations which could benefit from prolonged antigen delivery by replicating vectors [67]. Additionally, some Bet hybrids contained the FPPR derived E1 domain and the E2 domain linked by a loop to stabilise a MPER conformation that increases 2F5 binding [56,53,57,54].…”
Section: Discussionmentioning
confidence: 99%